Pengembangan Organisasi PT C Berdasarkan Tahap Pertumbuhan Organsiasi - Novia Lioe Herlina; Made Andriani (Journal of Research in Industrial Engineering and Management, 2023)
PT C is a fashion industry MSME located in Bandung, with declining sales and not growing business. This decline in sales has caused losses for the company, so there is a high urgency to make improvements immediately. There are various suspected causes of falling sales. Therefore, this study aims to analyze the company thoroughly, determine the priority of problems, and design interventions to improve the priority of these problems. The model used to conduct a thorough analysis and design improvements is the organizational development model, with stages of entering and contracting, diagnosing organizations, diagnosing groups and jobs, collecting and analyzing diagnostic information, feeding back diagnostic information, and designing interventions. In designing interventions, the direction of change is obtained by identifying organizational growth stages. The priority of problems obtained from diagnosing organizations, groups, and individuals is systems, processes, and strategies. Interventions designed to overcome these problems are strategic interventions in the form of organization design, strategy design, and technostructural interventions in the form of work design. Then, based on the identification of organizational growth stages, the company is currently between the entrepreneurial growth stage and collectivity. Therefore, the final result designed in this study is a strategy that can be implemented by the company, namely marketing and sales strategies. Next is the marketing and sales system and process that begins to be made into procedures, contributes to success, and aims to grow the company to make the company entirely at the collectivity stage.